Activity profile of top-class female soccer refereeing in relation to the position of the ball - Mallo, J.; Veiga, S.; Lopez de Subijana, C.; Navarro, E. (Journal of Science and Medicine in Sport, 2010)
The aim of this study was to describe the activity profile of top-class female soccer referees during competition and to relate it to the position of the ball. Ten matches from the Fédération Internationale de Football Association (FIFA) under-20 female World Championships held in Russia in 2006 were filmed and the kinematical parameters of the female referees (n = 10) and the ball were determined using a two-dimensional photogrammetric video system based on direct linear transformation (DLT) algorithms. Total distance covered during a match was 10 km, of which 1.3 km represented high-intensity activities (>13 km/h). The referees' highest mobility was achieved in the initial 15 min of the match, covering greater distance and performing more intense exercise (P < 0.01) than in the final 15-min of the game. Mean distance from the referee to the ball was 19.5 ± 2.4 m, with no significant differences between 15 min match periods. The results of this study show that: (1) the physical demands placed on top-class female referees are much like those experienced during male moderate-standard refereeing and (2) the referees were able to maintain the distance from the ball throughout the match.